High-precision U-Pb dating of complex zircon from the Lewisian Gneiss Complex of Scotland using an incremental CA-ID-TIMS approach - CROWLEY, QUENTIN (My University, 2015)
A novel approach of thermally annealing and sequentially partially dissolving single zircon grains prior to high-precision Isotope Dilution Thermal Ionization Mass Spectrometry (ID-TIMS) is presented. This technique is applied to complex zircon from the Precambrian Lewisian Gneiss Complex of Scotland. Up to six partial dissolutions were conducted at incrementally higher temperatures and analysed at each successive step. ID-TIMS analyses reveal the portions of zircon affected by the lowest temperature partial dissolution step have suffered Pb-loss. Successively higher temperature partial dissolution steps yield a series of analyses from the younger domains, followed by mixing trajectories with older components, presumably from the inner domains. Specifically, for a partially retrogressed granulite tonalite gneiss from the central block (Assynt), high-grade metamorphic zircon ages of c. 2500 Ma and c. 2700 Ma are resolved with a protolith age of c. 2860 Ma also recognised. This unequivocally demonstrates two separate episodes of high-grade metamorphism affected rocks from this region. The c. 2700 Ma age provides a minimum age constraint on the highest pressure event known from Archean crustal rocks. Using this technique of pseudo-spatial resolution coupled with high-precision analysis it is possible to recognise discrete Pb-loss and multiple stages of zircon growth or isotopic resetting within single grains to within 0.1–0.2% error (2σ) on individual 207Pb/206Pb ages. This method has relevance to U–Pb zircon geochronology where conventional micro-beam techniques are unable to resolve between separate ages within single grains.
PUBLISHED
Keywords: U–Pb zircon geochronology; CA-TIMS; Precambrian; Lewisian Gneiss; Smart & Sustainable Planet; Earth Science